Penggunaan Napier’s Bones untuk Keterampilan Perkalian Pembagian pada Siswa Low Average IQ - Siska Saskia Maharani; Sinta Verawati Dewi; Eko Yulianto (J-PiMat : Jurnal Pendidikan Matematika, 2026)
Research on mathematics education that specifically focuses on students with low-average IQs remains limited, even though these students require attention and appropriate learning strategies. This study aims to determine the effectiveness of using Napier’s bones in improving multiplication and division skills among students with low-average IQs. The research method employed a single-subject research (SSR) design with an A-B-A design, consisting of baseline-1, intervention, and baseline-2 phases. The research subject was a 10th-grade student with a low-average IQ who struggled with multiplication and division operations. The results of the study showed that the use of napier’s bones had a positive effect on improving the multiplication and division operation skills of the participant. This was evidenced by an increase in answer accuracy across each phase, from 20% correct answers in the baseline-1 phase to 99% in the baseline-2 phase. There was also a decrease in task completion time in each phase, accompanied by a trend toward improvement in the data and a low overlap of 0% between the baseline and intervention phases. These findings indicate that the use of napier’s bones as an intervention can significantly improve the participant’s multiplication and divition skills.Keyword: Napier’s Bones, Low average IQ, Perkalian dan Pembagian